Influence of pre-annealing Cu-Sn on the structural properties of CZTSe thin films grown by a two-stage process. (December 2018) - Olgar, M.A.; Başol, B.M.; Tomakin, M.; Seyhan, A.; Bacaksız, E.
Abstract: In this study CZTSe thin film were synthesized by a two-stage process that included sequential sputter deposition of Cu and Sn layers forming a Cu/Sn structure, pre-annealing the Cu/Sn structure at 200–380 °C for some of the samples, sputtering of additional Zn and Cu over the Cu/Sn structure, evaporation of a Se cap forming a Cu/Sn/Zn/Cu/Se precursor film, and exposing the precursor film to high temperature annealing treatment at 550 °C for 15 min to form the compound. The results of the characterization carried out on the compound layers revealed that the phase content, composition and microstructure of these layers changed noticeably depending on whether or not a pre-annealing step was utilized. Although XRD studies suggested presence of secondary phases, especially in the non-pre-annealed samples, the data was dominated by kesterite CZTSe phase reflections. Raman spectra of the films verified the formation of kesterite CZTSe structure and some other phases, which were determined to be SnSe2 and possibly ZnSe. SEM micrographs showed denser structure in the pre-annealed samples.